Model Aplikasi Peminjaman Ruangan Berbasis Web Pada Tingkat Fakultas di Perguruan Tinggi - Kadek Dika Sukmana; Ketut Queena Fredlina; Putu Trisna Hady Permana (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2022)
The procedure for borrowing a room which is still done manually at the faculty level in Higher Education causes the borrowing process to be inefficient, because all matters must go to the service officer directly. The research aims to develop a Web-based application model that can be used in the process of borrowing rooms at faculty level managers in universities, without having to go to service officers, so that the borrowing process becomes more effective and efficient. Application development uses the SDLC (Software Development Life Cycle) method. The case study was conducted at the Faculty of Economics and Business, Udayana University. The system modeling uses structured modeling tools, while the system construction uses the PHP programming language, JavaScript, and MySQL database. The main functional features identified at the requirements analysis stage are the system's ability to provide an online room loan interface, room loan statistics, and room loan reports for faculty management. The results of the functional test using Blackbox Testing show that all functional features available in the application have functioned validly.Keywords: Software; Software Development Life Cycle; Functional testing; Black box testing Abstrak. Prosedur peminjaman ruangan yang masih dilakukan secara manual pada tingkat fakultas di perguruan tinggi menyebabkan proses peminjaman menjadi tidak efisien, karena segala urusan harus mendatangi petugas pelayanan secara langsung. Penelitian bertujuan mengembangkan model aplikasi berbasis web yang dapat digunakan dalam proses peminjaman ruangan pada pengelola tingkat fakultas di Perguruan Tinggi, tanpa harus mendatangi petugas pelayanan, sehingga proses peminjaman menjadi lebih efektif dan efisien. Pengembangan aplikasi menggunakan metode SDLC (Software Development Life Cycle). Studi kasus dilakukan pada Fakultas Ekonomi dan Bisnis Universitas Udayana. Pemodelan sistem menggunakan tools pemodelan terstruktur, sedangkan konstruksi sistem menggunakan bahasa pemrograman PHP, JavaScript, dan basis data MySQL. Fitur fungsional utama yang diidentifikasi pada tahap analisis kebutuhan berupa kemampuan sistem menyediakan antarmuka peminjaman ruangan secara online, data statistik peminjaman ruangan, serta laporan peminjaman ruangan bagi manajemen Fakultas. Hasil uji fungsional menggunakan Black box testing menunjukkan seluruh fitur fungsional yang tersedia pada aplikasi telah berfungsi secara valid.Kata kunci: Perangkat lunak; Software Development Life Cycle; Uji fungsional; Black box testing